A major plant practice in Mead Johnson Nutritionals a Division of Bristol Myers Squibb (Phils.), Inc., at 2309 Don Chino Roces Avenue, Extension, Makati City, Philippines - Enarsico, Joahna Marie Coronel (2003)
The 288 hours of plant practice in the Mead Johnson Nutritionals located at 2309 Don Chino Roces Avenue, Extension, Makati City, Philippines, which was a division of Bristol- Myers Squibb (Phil.), Inc. enabled the author to apply all the theories and principles she accumulated while taking up the food technology degree program. She had her first encounter in the warehouse operation and production support group where raw materials are carefully handled, received and stored. She was then exposed to the quality assurance department of the company. Furthermore, she had a hands-on training in the production unit of the company. In addition, she also became part of the quality control group of the company. The plant practice was overwhelming with acquisition of training in the technical aspect of producing goods as well as the services offered by their business. Information regarding the company was gathered and some problems were distinguished. Afterwhich, recommendations were raised. The author enjoyed the knowledge and fun-filled experience within 37 days of on-the-job training in the said firm